2014
DOI: 10.1115/1.4027917
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Magnetic Pulse Welding of Al/Cu and Interface Characterization

Abstract: This paper investigated the effect of magnetic pulse welding (MPW) condition (welding power, surface scratches, and contamination) on the establishment of welding between aluminum and copper tubes, and the associated welding mechanisms. The results showed that higher applied power and surface scratches in tangential direction were in favor for good weld, and oil on the surface prevented welding. Direct evidences were obtained on local interface melting under a high welding power. CuAl intermetallics with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This means that the jet formation during the MPW process was influenced by the presence of oil and threads. Regarding this effect on the lubricated surface, it is consistent with another research [12]. The energy has not been sufficient to remove the contamination and to produce a wavy pattern.…”
Section: Microstructure Of Interfacessupporting
confidence: 89%
See 2 more Smart Citations
“…This means that the jet formation during the MPW process was influenced by the presence of oil and threads. Regarding this effect on the lubricated surface, it is consistent with another research [12]. The energy has not been sufficient to remove the contamination and to produce a wavy pattern.…”
Section: Microstructure Of Interfacessupporting
confidence: 89%
“…Moreover, micro or sub micro scale local melting and solidification can also be considered as the bonding mechanism for MPW, however, this depends on the level of the input energy [11]. In addition to the processing parameters, geometrical designs, and materials characteristics, some researches were conducted to evaluate the influence of the surface preparation on the bonding quality for the MPW process [12][13][14][15] as summarized in Table 1. However, there are two studies that clearly presented the influence of pre-treatments on the joint quality [12,14], and the other two works mentioned that the processing conditions such as impact angle strongly determine the weld quality [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifi cally, there is a need to develop a manufacturing process in which coupled electromagnetic and mechanical forces are applied. The application of electromagnetic forces in metal forming and weld ing was reported and quality improvement on material processing was discussed [21], In this technical note, it is shown that centrifu gal casting with a newly designed rotary machine can generate the mechanical forces needed. The electric force is added by using a high voltage direct current (DC) power source.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, vehicle lightweighting has played a key part in energy saving and environment protection in the transportation industry [1,2,3,4]. Aluminum alloys, as an important type of lightweight material, have become increasingly popular due to their high strength-to-weight ratio, good formability, machinability and recyclability [5].…”
Section: Introductionmentioning
confidence: 99%